EE II 2 1220a39”“b6 - Ferreira, Paulo Fernando Tadeu (Revista Archai, 2017)
Aristotle's Eudemian Ethics has always proved to be fertile ground for at times needless textual emendation. I provide a translation and running commentary on Eudemian Ethics II 2 1220a39”“b6 in accordance with the MSS text.